2018
DOI: 10.1002/gj.3198
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology and geochemistry of the Carboniferous felsic rocks in the central Great Xing'an Range, NE China: Implications for the amalgamation history of Xing'an and Songliao–Xilinhot blocks

Abstract: The tectonic evolutionary history between the Xing'an Block (XB) and Songliao-Xilinhot Block (SXB) has been hotly debated. Here, we present precise geochronological ages and whole-rock geochemical data in the central Great Xing'an Range for the Carboniferous felsic rocks to reveal this tectonic history, as the petrogenesis of these rocks were closely related to tectonic activity between the XB and SXB. The age data with detailed geochemical analyses indicate three important stages of magmatism: early Carbonife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 103 publications
2
15
0
Order By: Relevance
“…However, the sedimentary record in Jalaid Banner and adjacent areas of the western SXB from the Late Devonian to early Carboniferous is poorly known, and further research is needed to establish a more detailed and accurate record. Following the amalgamation of the XAC and SXB (Liu et al, 2017, 2019; Ma et al, a), sedimentation occurred in the central Great Xing'an Range, with deposition of the Baoligaomiao and Gegenaobao formations during the late Carboniferous and of the Dashizhai, Zhesi, and Linxi formations during the Permian. A ductile shear zone has been identified in western Jalaid Banner (Qin et al, ), as revealed by mylonitization in Late Devonian and early Carboniferous granites (Figure ).…”
Section: Geological Background Samples and Petrographymentioning
confidence: 99%
See 3 more Smart Citations
“…However, the sedimentary record in Jalaid Banner and adjacent areas of the western SXB from the Late Devonian to early Carboniferous is poorly known, and further research is needed to establish a more detailed and accurate record. Following the amalgamation of the XAC and SXB (Liu et al, 2017, 2019; Ma et al, a), sedimentation occurred in the central Great Xing'an Range, with deposition of the Baoligaomiao and Gegenaobao formations during the late Carboniferous and of the Dashizhai, Zhesi, and Linxi formations during the Permian. A ductile shear zone has been identified in western Jalaid Banner (Qin et al, ), as revealed by mylonitization in Late Devonian and early Carboniferous granites (Figure ).…”
Section: Geological Background Samples and Petrographymentioning
confidence: 99%
“…The evolution of convergence between the XAC and the SXB is closely associated with the history of narrowing and closure of the Nenjiang Ocean (NJO, the paleo‐oceanic basin between the XAC and the SXB; Liu et al, 2017; Ma et al, a; Xiao et al, ). Previous studies have typically regarded the NJO as a northern branch of the Paleo‐Asian Ocean (e.g., Liu et al, 2017; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is lack of ophiolitic rocks along the boundary between the Xing'an Block and Songliao Block, which has raised long‐time arguments for the location and timing of the boundary (Y. Liu et al, ; Y. Ma et al, ; B. Xu & Xu, ). Shi et al () report several A‐type granites along the boundary in the Yili area in the northern Great Xing'an Range.…”
Section: Tectonics Of Eastern Chinamentioning
confidence: 99%